The political pulpit: issue framing and conservative partisanship in evangelical protestant pastors' sermons before and after the 2008 election of Barack Obama - Stokes, Ethan C. (Church, Communication and Culture, 2018)
The intersection between religion and politics in the United States remains prevalent in the 21st century. Especially in regard to many Protestant Christian denominations, the relationship between religion and political partisanship seems to continually intensify. Through a content analysis of online sermon transcripts, this study focuses on Protestant pastors' interpretations of numerous political issues in the 21st century U.S. both before and after the 2008 election of President Obama. Drawing from framing theory, the majority of pastors primarily framed their sermons in three main ways: (1) increased discussions of political conservatism after the 2008 election, (2) maintained abortion as the most popular social issue discussed, and (3) increased discussions of literalist interpretations of the U.S. Constitution following the 2008 election. The study's results and implications for various avenues of future research are discussed at length.